2008
DOI: 10.2527/jas.2007-0262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of an enzyme blend on the ileal and fecal digestibility of nutrients in growing pigs1

Abstract: The objective of this experiment was to determine the effect of a beta-glucanase-protease enzyme blend product (EBP) on fecal digestibility (FD), apparent ileal digestibility (AID), standardized ileal digestibility, and digestibility in the hindgut of growing pigs. Twelve ileal-cannulated, growing barrows (38.2 +/- 0.5 kg) were housed in individual metabolism crates, blocked by previous feed intake into 3 groups with 4 pigs each, and randomly assigned to 1 of 4 treatments within a square (group) of 3 replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 35 publications
5
41
1
4
Order By: Relevance
“…High levels of NSP in pig diets can cause an increase in digesta viscosity, preventing interaction between substrate and digestive enzymes and, hence, reducing the nutrient digestibility (O'Connell et al, 2005;Passos et al, 2015). Previous studies demonstrated that supplementation of exogenous enzymes to high-NSP diets reduced the viscosity of digesta and enhanced the nutrient utilization (Parkkonen et al, 1997;Grandhi, 2001;Ji et al, 2008;Tapingkae et al, 2008). In the present study, pigs fed diets supplemented with β-mannanase had greater digestibility of β-mannan, which might reduce digesta viscosity and improve nutrient utilization.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…High levels of NSP in pig diets can cause an increase in digesta viscosity, preventing interaction between substrate and digestive enzymes and, hence, reducing the nutrient digestibility (O'Connell et al, 2005;Passos et al, 2015). Previous studies demonstrated that supplementation of exogenous enzymes to high-NSP diets reduced the viscosity of digesta and enhanced the nutrient utilization (Parkkonen et al, 1997;Grandhi, 2001;Ji et al, 2008;Tapingkae et al, 2008). In the present study, pigs fed diets supplemented with β-mannanase had greater digestibility of β-mannan, which might reduce digesta viscosity and improve nutrient utilization.…”
Section: Discussionsupporting
confidence: 51%
“…The positive effects of exogenous enzymes are quite variable and seem to depend on physiological status of the pigs and the content of NSP (Ji et al, 2008;Li et al, 2010;Adeola and Cowieson, 2011). Therefore, exogenous enzymes should be selected on the basis of type and amount of the NSP in the pig diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the results of in vitro tests, the addition of enzyme complexes (xylanase, protease and phytase) tended to increase the ileal digestibility of dry matter, even though it depended on test ingredients (Kong et al, 2015). Other studies also showed that enzyme mixtures including protease had a positive impact on nutrient digestibility, bacterial populations in the large intestine, and growth performance of weaned pigs (Yi et al, 2013), faecal nutrient digestibility of growing pigs (Ji et al, 2008), and the performance of growing pigs without improving apparent total tract digestibility (Jo et al, 2012). Recently, standalone proteases of swine diets have been used via several commercially available products (Guggenbuhl et al, 2012;Mc Alpine et al, 2012a, 2012bZuo et al, 2015).…”
Section: Resultsmentioning
confidence: 88%
“…Protease, a dietary enzyme, has been used generally in swine diets for many years as part of enzyme cocktails (Zuo et al, 2015). Most studies on protease supplementation in swine diet have shown positive effects on nutrient digestibility and growth performance (Ji et al, 2008;Jo et al, 2012;Omogbenigun et al, 2004;Yin et al, 2004Yin et al, , 2001Zuo et al, 2015). Recently, standalone proteases have been available commercially and have shown beneficial effects on nutrient digestiblity and growth performance of pigs (Adeola & Cowieson, 2011;Guggenbuhl et al, 2012;Mc Alpine et al, 2012a;O'Doherty & Forde, 1999;Zuo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%